Experimental implementation of a new multi input multi output fuzzy-PID controller in a poultry house system - Ilyas Lahlouh; Fathlah Rerhrhaye; Ahmed Elakkary; Nacer Sefiani (Heliyon, 2020)
Broiler house systems are operated for the primary purpose of providing the appropriate conditions suitable to have a significant efficiency of animal production. The major environmental conditions in the poultry building are controlling the hygro-thermal parameters (temperature and relative humidity) and contaminant gases (NH3, CO2). In this paper, a poultry house prototype is monitored and controlled using the Supervisory Control and Data Acquisition (SCADA) tool like LabVIEW. A full prototype is designed and an efficient hybrid control strategy is implemented to control in real-time the poultry house climate. In the suggested approach, a Multi-Input Multi-Output (MIMO) fuzzy logic controller (FLC) is combined with a proportional, integral, derivative (PID) controller tuned by fuzzy rules. The proposed method, fuzzy logic, and On/Off controllers were tested by experimental measures and studies in a prototype model over 30 days during hot climates. The comparison results showed that the root mean square error of temperature and relative humidity response with the MFLPID controller (0.8 °C, 1.34%) were lower than that of FLC (1.16 °C, 1.86%) and On/Off controller (2.09 °C, 3.08%). The mean value of CO2 concentration with MFLPID (2461 ppm) was lower than that of FLC (3294 ppm) and On/Off controller (3624 ppm). However, the mean value of NH3 concentration was limited in small value (<5 ppm) for all controllers. The performance of the daily weight gained by the chickens for the MFLPID system was found to be 97%, which is higher than that of FLC (88%) and On/Off (80%). The energy consumption of the actuators can be saved at 43% and 14% with MFLPID compared to the On/Off and fuzzy controllers. These results indicate that the proposed control strategy is more efficient in the application of the poultry farming sector.